A hybrid method for a family of quasi-nonexpansive and lipschitz multi-valued mappings - Suthep Suantai (2018)
Our purpose in this paper is first to study a mapping which is generated by a family of quasinonexpansive and Lipschitz multi-valued mappings. Further, using the shrinking projection method, we establish strong convergence theorems for solving fixed point problems of such mappings. Copyright © 2012 Watam Press.